2015
DOI: 10.1016/j.ultsonch.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted combustion synthesis of TiC in Al–Ti–C system

Abstract: This research investigated the effects of high-intensity ultrasound on the combustion synthesis of TiC particles in Al-Ti-C system. The process involved that high-intensity ultrasound was applied on the surface of a compacted Al-Ti-C pellet directly through a Nb probe during the thermal explosion reaction. By comparing with the sample without ultrasonic treatment, it was found that the thermal explosion reaction for synthesizing TiC phase could take place thoroughly in the ultrasonically treated sample. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…The formation of TiO 2 (Equation (1)) is easier than that of TiC (Equation (2)), evidenced by the higher enthalpy in Table 2, and the formation of TiO 2 releases a higher heat amount for subsequent combination of TiC, leading to the obviously enhanced characteristic peaks corresponding to TiC. Besides, the subsequent reduction reaction between CO (derived from the transformation of impurities in CB) and Ti left preferentially occurs, as in Equation (6), due to the higher Gibbs enthalpy (Equations (3)-(5)) not occurring (due to their positive ∆Gs), which is completely consistent with the literature [33,34]. But the oxidation of TiC takes place as Equation (8), due to the higher ∆H and ∆G than that of Equation (7) above 973 K, leading to the absence of TiC for S3.…”
Section: Discussionsupporting
confidence: 87%
“…The formation of TiO 2 (Equation (1)) is easier than that of TiC (Equation (2)), evidenced by the higher enthalpy in Table 2, and the formation of TiO 2 releases a higher heat amount for subsequent combination of TiC, leading to the obviously enhanced characteristic peaks corresponding to TiC. Besides, the subsequent reduction reaction between CO (derived from the transformation of impurities in CB) and Ti left preferentially occurs, as in Equation (6), due to the higher Gibbs enthalpy (Equations (3)-(5)) not occurring (due to their positive ∆Gs), which is completely consistent with the literature [33,34]. But the oxidation of TiC takes place as Equation (8), due to the higher ∆H and ∆G than that of Equation (7) above 973 K, leading to the absence of TiC for S3.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the XRD analysis, as shown in Figure 5. According to the thermodynamic analysis of the Al–Ti–C system [34], it is clear that the TiC phase was more thermodynamically stable than the Ti–Al phases due to its lower △G. Therefore, during the formation of the diffusion layer, the TiC phase will be excised in the diffusion layer when the Ti–Al phases are formed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were some unreacted graphite particles in the final product, as shown in Figure 9c. Recently, Liu et al found that ultrasound is able to promote combustion synthesis reactions in the Al-Ti-C system to be more complete [81]. High-intensity ultrasound could accelerate the formation of a saturated solution of C atoms in the Al–Ti melt, and the nucleation and growth of TiC could also be promoted.…”
Section: The Synthesis and Characterization Of Three-dimensional Tmentioning
confidence: 99%
“…In previous studies, graphite particles of approximately 5 μm, 15 μm, 38 μm or even 48 μm were reported as used to fabricate TiC [30,75,80,86]. Becasuse graphite has a large size, it always becomes a residual phase in the reactant and has not been completely reacted with Ti, except for via some special measures [81]. Wang et al suggested that the residual graphite in the reactant was actually graphite flake agglomerations [87].…”
Section: The Synthesis and Characterization Of Three-dimensional Tmentioning
confidence: 99%